Resveratrol Increases Serum BDNF Concentrations and Reduces Vascular Smooth Muscle Cells Contractility via a NOS-3-Independent Mechanism - Michał Wiciński (BioMed Research International, 2017)
Resveratrol is a polyphenol that presents both antineuroinflammatory properties and the ability to interact with NOS-3, what contributes to vasorelaxation. Brain-derived neurotrophic factor (BNDF), a molecule associated with neuroprotection in many neurodegenerative disorders, is considered as an important element of maintaining stable cerebral blood flow. Vascular smooth muscle cells (VSMCs) are considered to be an important element in the pathogenesis of neurodegeneration and a potential preventative target by agents which reduce the contractility of the vessels. Our main objectives were to define the relationship between serum and long-term oral resveratrol administration in the rat model, as well as to assess the effect of resveratrol on phenylephrine- (PHE-) induced contraction of vascular smooth muscle cells (VSMCs). Moreover, we attempt to define the dependence of contraction mechanisms on endothelial NO synthase. Experiments were performed on Wistar rats (n=17) pretreated with resveratrol (4 weeks; 10 mg/kg p.o.) or placebo. Serum BDNF levels were quantified after 2 and 4 weeks of treatment with ELISA. Contraction force was measured on isolated and perfused tail arteries as the increase of perfusion pressure with a constant flow. Values of serum BNDF in week 0 were 1.18±0.12 ng/mL (treated) and 1.17±0.13 ng/mL (control) (p = ns). After 2 weeks of treatment, BDNF in the treatment group was higher than in controls, 1.52±0.23 ng/mL and 1.24±0.13 ng/mL, respectively. (p=0.02) Following 4 weeks of treatment, BDNF values were higher in the resveratrol group compared to control 1.64±0.31 ng/mL and 1.32±0.26 ng/mL, respectively (p=0.031). EC50 values obtained for PHE in resveratrol pretreated arteries were significantly higher than controls (5.33±1.7 × 10−7 M/L versus 4.53±1.2 × 10−8 M/L, p<0.05). These results show a significant increase in BDNF concentration in the resveratrol pretreated group. The reactivity of resistant arteries was significantly reduced for resveratrol pretreated vessels and this effect was partially NOS-3 independent.